Factors in the occurrence and restoration of hypoparathyroidism after total thyroidectomy for thyroid cancer patients with intraoperative parathyroid autotransplantation - Lu, Dengwei; Tang, Enjie; Yin, Supeng; Zhu, Junping; Mo, Hongbiao; Yi, Ziying; Chai, Fan; Sun, Yizeng; Li, Yao; Yin, Tingjie; Yang, Zeyu; Zhang, Fan (Frontiers in Endocrinology, 2022)
Abstract Introduction: Postoperative hypoparathyroidism (POH) is the most common and important complication for thyroid cancer patients who undergo total thyroidectomy. Intraoperative parathyroid autotransplantation has been demonstrated to be essential in maintaining functional parathyroid tissue, and it has clinical significance in identifying essential factors of serum parathyroid hormone (PTH) levels for patients with parathyroid autotransplantation. This retrospective cohort study aimed to comprehensively investigate influential factors in the occurrence and restoration of POH for patients who underwent total thyroidectomy with intraoperative parathyroid autotransplantation (TTIPA). Method: This study was conducted in a tertiary referral hospital, with a total of 525 patients who underwent TTIPA. The postoperative serum PTH levels were collected after six months, and demographic characteristics, clinical features and associated operative information were analyzed. Results: A total of 66.48% (349/525) of patients who underwent TTIPA were diagnosed with POH. Multivariate logistic regression indicated that Hashimoto's thyroiditis (OR=1.93, 95% CI: 1.09-3.42), P=0.024), the number of transplanted parathyroid glands (OR=2.70, 95% CI: 1.91-3.83, P<0.001) and postoperative blood glucose levels (OR=1.36, 95% CI: 1.06-1.74, P=0.016) were risk factors for POH, and endoscopic surgery (OR=0.39, 95% CI: 0.22-0.68, P=0.001) was a protective factor for POH. Multivariate Cox regression indicated that PTG autotransplantation patients with same-side central lymph node dissection (CLND) (HR=0.50; 95% CI: 0.34-0.73, P<0.001) demonstrated a longer time for increases PTH, and female patients (HR=1.35, 95% CI: 1.00-1.81, P=0.047) were more prone to PTH increases. Additionally, PTG autotransplantation with same-side CLND (HR=0.56, 95% CI: 0.38-0.82, P=0.003) patients had a longer time to PTH restoration, and patients with endoscopic surgery (HR=1.54, 95% CI: 1.04-2.28, P=0.029) were more likely to recover within six months. Conclusion: High postoperative fasting blood glucose levels, a large number of transplanted PTGs, open surgery and Hashimoto's thyroiditis are risk factors for postoperative POH in TTIPA patients. Elevated PTH levels occur earlier in female patients and patients without CLND on the transplant side. PTH returns to normal earlier in patients without CLND and endoscopic surgery on the transplant side.